The Effect of Unemployment and Poverty on Economic Growth in Mamasa Regency: Pengaruh Pengangguran dan Kemiskinan Terhadap Pertumbuhan Ekonomi di Kabupaten Mamasa - Siti Alfiah; Abdul Rajab; Ernawaty Mappigau (Jurnal Actual Organization Of Economic, 2023)
Mamasa Regency is one of the areas where most of the people are still unable to meet their primary and secondary needs because many still do not have jobs, so that many residents are still unable to meet their daily needs. Unemployment and poverty that occur in Mamasa Regency will have an impact on economic growth in the region because it does not experience an increase as it should to help the development of the village and the Mamasa district area. This study aims to confirm the effect of unemployment and poverty on economic growth in Mamasa District. The research method uses quantitative methods with secondary data using time series. The data obtained will be analyzed using multiple linear regression, partial test and simultaneous test. From the time series data, it was carried out using multiple linear regression methods, the F test and the t test. the results of the analysis reveal that the variables of unemployment and poverty have an effect but not significant on economic growth. The results analyzed for the value of unemployment, poverty and economic growth with data for the last 10 years show the results of SPSS with a negative value with a significance level greater than the specified standard error.